From investigations of interrelations between formulas of fingers and of toes - Arska-Kotlińska, Małgorzata; Drozdowski, Zbigniew (Anthropological Review, 1977)
The authors have examined relative lenghts of II and IV fingers and I-II toes in a group of 968 adult males and 594 adult females. Each individual was described with use of commonly known in literature formulas: for toes — 1>2, 1=2, 1<2, for fingers 2>4, 2=4, 2<4. The results are shown in the table. The authors have found that certain finger formulas are correlated with certain toe formulas, this interdependence being somewhat different in various sex and age groups.